(untitled) (Journal of the College of Basic Education, 2024)
Was Isolated Diagnosis of bacteria from drinking water models mansuriyah – shat –village- the Qasiris and the village of Al –Hawish along the Tigris River . where water was collected from the River . the study period was six months , November to April . In this study the focus was on the most important pathological bacteria Harmful . which affects human health , Especially cases of severe Diarrhoea and transported through the water for human beings . Human beings are a means of transmission Enterobacter , it s’ this bacteria , Escherichia coli , Sp Pseudomonas , SP Klepsiella , Shigella , Enterobacteraerogenes , Clostridium Perifringens ,Vibrio Cholera and Aeromonas SP, the presence of these microscopic organisms proof of water pollution . some chemical and biological factore have also been studied like the chemical requirment of oxygen COD , and the biological requirmentb of oxygen BOD and total outstanding materials . as well as the study of biological factors of the environments under study . found through results and abiotic factors . specifications of water samples taken from all stations from temperature (32-12)C°and salinity (0.1-0.5)G/L , AND Ph (8.4-9.4)COD (21-13)ppm and BOD (18-6)ppm. The results of abiotic factors are encouraging for bacteria growth in the invironments under study the results show that the River Tigris water is contaminated or highly contaminated . they are in appropriate as asource of drinking water , without multiple processing